MODEL OF THE RELATIONSHIP BETWEEN EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN THE WORKFORCE LAU GUMBA TOURISM INDUSTRY, BERASTAGI DISTRICT - Wakhyuni, Emi; Nurhayati, Siti; Rafianti, Fitri; Tarigan, Kevin (Proceeding International Seminar of Islamic Studies, 2024)
Employee engagement is a concept that describes the level of employee involvement in their work. Organizational citizenship behavior is employee behavior that is not explicitly defined in the employment contract, but contributes positively to organizational effectiveness. This study aims to analyze the relationship model of employee engagement with the tourism industry workforce of Lau Gumba Village, Berastagi District. This study used a survey method with respondents as many as 20 workers of the Lau Gumba Village Tourism Industry. The results showed that employee engagement has a positive and significant influence on organizational citizenship behavior. In addition, this study also found that there are two mediating variables that affect the relationship between employee attachment and organizational citizenship behavior, namely; quality of labor relations and perception of fairness. The quality of good working relationships between Lau Gumba Village tourism industry workers and their leaders can increase the attachment of all workers which in turn can improve organizational citizenship behavior. High perceptions of fairness can also increase workforce engagement which in turn can improve organizational citizenship behavior. Based on the results of this study, it is recommended to the Lau Gumba Village Government to increase the engagement of the tourism industry workforce by improving the quality of labor relations and perceptions of justice. Increasing workforce engagement can be done in various ways, such as providing opportunities for self-development, creating a positive work environment, and providing fair rewards.